The myth of contributive capacity: Brief comments regarding to the current regulation to Income Tax Individuals and a proposal for the future - Meneses Morales, Indhira (2015)
This paper aims at analyzing the current regulation of the income Tax of Individuals from a critical point of view of its effects on taxpayers’ ability to pay. Also, it propose a different solution to the current model of taxation in our country, which is found more accordance with the wealth of the taxpayers.